Narratives to revert overconsumption: human-nature interdependence and Circular Economy - M. Borrello; L. Cembalo; V. D’Amico (Agricultural and Food Economics, 2023)
Abstract Policy and practitioners’ initiatives to stimulate sustainable consumption have so far failed to have notable impact on individuals’ behaviors. The current commentary is a plea to social and sustainability scientists, particularly to economists dealing with sustainable agri-food systems, to dig deeper into the notion of narratives to trigger societal dynamics that stir consumers toward more sufficient lifestyles. As dominant cultural narratives have a critical role in shaping shared meanings and acceptable behaviors, in the future they could guide dramatic changes in individuals’ conduct, triggering drastic modifications of current consumption patterns. Based on the power that concepts as the Circular Economy and the Anthropocene have had in the recent past, a future step to develop an ecological worldview across society, and nourish individual identities deeply committed with the preservation of natural ecosystems, is working on narratives based on the notion of human-nature interdependence.